The peculiarities of mathematic communication of the eight-formers - Sičiūnienė, Viktorija (Lietuvos matematikos rinkinys, 2023)
The national research of 2005 revealed that in the eighth form the achievements in algebra are lower than in other fields of mathematics. The results of the boys are statistically much lower compared to the girls (the author of the article is a member of the research group). The possibility of the eighth-formers (boys and girls) to solve problems in algebra are analyzed and compared in the article. The research included 2146 students. The students were given 16 problems to solve and the girls coped with them approximately 7–12 percent better than the boys. The girls compared with the boys, performed standard operations better, made less mistakes in combining them, and most often carried out them consecutively. The boys did not solve problems and exercises in mathematics especially if the tasks had operations with fractions. The tasks of concrete content containing small numbers were tried to be solved more by the boys. However, to solve them the boys most frequently choose an arithmetic way and wrote down only the answer. It is evident that the period of transition from concrete perception to the abstract one is at an average later for boys than girls. Boys accept loads of abstract notions in algebra more difficult. The authors of textbooks and teachers should pay attention to is phenomenon.